Lecturers, philosophy, and classrooms: The struggles of the four schools of educational thought in teaching practices - Marzulina, Lenny; Purnomo, Mulyadi Eko; Sumarni, Sri; Maharani, Siti Dewi (Indonesian Research Journal in Education |IRJE|, 2025)
This study aims to explore the philosophical orientations underlying the teaching practices of lecturers in Islamic higher education in South Sumatra. The study focuses on how lecturers interpret and integrate moral, rational, pragmatic, and reflective dimensions in their learning process. Using a descriptive qualitative approach, data were collected through semi-structured interviews with nine lecturers from three study programs at the Faculty of Islamic Education. Data were analyzed thematically to identify patterns of meaning emerging from participants' experiences. The results indicate that lecturers' philosophical orientations are dynamic and interwoven; spiritual values ​​and moral ethics are combined with scientific rationality, pedagogical flexibility, and a reflective awareness of the meaning of the profession. These findings confirm that philosophical awareness is still alive and plays a significant role in shaping lecturers' professional identities and pedagogical decisions. This study provides a conceptual contribution to strengthening Islamic higher education by emphasizing the importance of lecturer professional development based on philosophical reflection.